PERAN ORANG TUA DALAM PENDIDIKAN ANAK PERSPEKTIF Al-QUR’AN - NurFajriah, Inayah nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Children’s education is primarily the responsibility of parents, as they are the first and foremost educators in a child's life. In Islam, the concept of education begins even before a child is born, as reflected in various verses of the Qur’an. However, in this modern era filled with challenges, the role of parents in child education is increasingly being overlooked. This study aims to examine in depth the role of parents in children's education based on the perspective of the Qur’an. This research employs a descriptive method with a library approach, analyzing verses from the Qur’an along with classical and contemporary interpretations such as Tafsir al-Jalalayn and Tafsir al-Misbah. The findings indicate that parents play a crucial role in instilling the values of faith (aqidah), worship (ibadah), and morals (akhlaq) in their children. According to the Qur’an, child education begins in the womb and continues after birth through the habituation of worship, strengthening of monotheism (tawhid), and character development. The implementation of these values is not only carried out through teaching but also through the parents’ daily example.